Proposed Business Development Strategy for Enhancing Profitability of CV. Kharisma Satria Lestari - Maria Ambalika Setiadi; Harimukti Wandebori (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Indonesia’s textile industry has experienced a significant decline, reflected in the rising number of bankrupt companies, large-scale layoffs, and reduced factory utilization rates. This contraction has sharply reduced the demand for textile machinery spare parts, which directly affects CV. Kharisma Satria Lestari (KSL), a supplier of spare parts for textile manufacturers. The company has faced a shrinking client base, a substantial drop in order volume, and revenue decline of 37.5 percent. This study aims to formulate an appropriate business development strategy to enhance CV.KSL’s profitability. This research adopts a qualitative approach through semi-structured interviews, participant observations, and literature review. The findings show that CV. KSL’s heavy dependence on a single customer segment, integrated production medium to large textile companies, has made the company highly vulnerable to downturns. The weak market condition also amplifies the bargaining power of buyers, posing a major challenge for CV. KSL. Competitive pressure from existing rivals and potential entrants further intensifies this situation. Internally, the company struggles with limited resources, outdated production machinery, and centralized decision-making processes that reduce agility and innovation. To address these challenges, a broader differentiation strategy is recommended. CV. KSL should expand its client acquisition efforts within its current target segment while also reaching new segments, particularly small-scale textile firms that demonstrate high demand for spare-part repair and replacement. Successful implementation requires strengthening digital marketing, networks, and R&D capabilities to support product enhancement, which creates added value that distinguishes KSL from competitors, ultimately improving its profitability.